The rise in comovement across national stock markets: market integration or IT bubble? - Robin Brooks; Marco Del Negro (Federal Reserve Bank of Atlanta, 2002)
A stylized fact in the portfolio diversification literature is that diversifying across countries is more effective than diversifying across industries in terms of risk reduction. But with the rise in comovement across national stock markets since the mid-1990s, this no longer appears to be true. We explore whether this change is driven by global integration and therefore likely to be permanent, or if it is a temporary phenomenon associated with the recent stock market bubble. Our results point to the latter hypothesis. In the aftermath of the bubble, diversifying across countries may therefore still be effective in reducing portfolio risk.
Keywords: 330; Financial markets; Risk; Markets